Ethics of Artificial Intelligence Usage in the Judiciary to Uphold Efficiency and Justice - Arbani, Tri Suhendra (Center for Maritime Policy Governance Studies (CMPGS), 2025)
The adoption of Artificial Intelligence (AI) in the judiciary has sparked significant interest due to its potential to enhance efficiency and accuracy in legal processes. However, this advancement also brings ethical concerns that demand careful attention. This paper examines key ethical issues surrounding AI usage in judicial systems, including the risks of algorithmic bias, the lack of transparency in decision-making processes, and the possible erosion of human judgment. It highlights the importance of maintaining accountability and fairness while integrating AI tools to support, not replace, the role of judges. Using real-world examples and analyzing existing legal frameworks, the discussion emphasizes the need to align AI innovation with the fundamental principles of justice and human rights. The findings of this paper aim to provide practical insights for legal professionals, policymakers, and AI developers to establish ethical guidelines that ensure AI contributes to a fair and equitable judiciary. Balancing efficiency with justice remains the central goal of this exploration.